Synthesis and biological evaluation of novel N-pyridylpyrazole derivatives containing 1,2,3-triazole moieties - Mao, Mingzhen; Li, Yuxin; Liu, Qiaoxia; Xiong, Lixia; Zhang, Xiao; Li, Zhengming (Journal of Pesticide Science, 2015)
Based on the commercial insecticide chlorantraniliprole, a series of novel N-pyridylpyrazole derivatives containing 1,2,3-triazole moieties were designed and synthesized via Huisgen cycloaddition reaction. The insecticidal activities of the new compounds against the oriental armyworm (Mythimna separata) were evaluated, of which compound Ib with an N-isopropyl anthranilic amide moiety displayed 100% larvicidal activities against Mythimna separata at a concentration of 10 mg/L. Moreover, the fungicidal activities of some target compounds in vitro against five fungi at 50 µg⁄mL indicated that some compounds exhibited moderate fungicidal activities.